Daniel the prophet and the time of the Gentiles - Dennett, Edward, 1831-1914 (London, UK A.S. Rouse, 1893)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. O.T. Daniel -- criticism, interpretation, etc